Sport and physical activity in the urban area - housing estate greens for three generations - Anna Ostrowska-Tryzno; Hanna Nałęcz; Anna Pawlikowska-Piechotka (Jan Długosz University in Częstochowa, 2020)
Research aim: Playgrounds were historically designed only for children, today we can observe new concept of recreation sites, aimed for all ages. Traditional playground was furniture with kids' equipment, while universal playgrounds have also facilities for adults. These facilities enable families to play together. Research methods: Research project ds-300 AWF was a continuation of the ds-114 AWF - the MNiSW grant. Using the field survey with participant observations, structured and semi-structured interviews methods, factors determining the 'inclusive urban playground' for three generations were identified. Research results: To achieve the open access to the universally designed, inclusive playgrounds for all ages, basic components should be included: physical accessibility, age and developmental appropriateness, physical, social and sensory-stimulating components. Conclusions: Results show that exciting, engaging and challenging sport and recreation housing green areas are important to encourage physical activities for all age and enhance social, mental and physical skills of the three generations.